Goat [videorecording (DVD)] - Neel, Andrew; Jonas, Nick; Schnetzer, Ben, 1990-; Franco, James, 1978- (Paramount, 2016)
Reeling from a terrifying assault over the summer, nineteen-year-old Brad Land starts college determined to get his life back to normal. His brother, Brett, is already established on campus and in a fraternity that allures Brad, who is desperate to belong. As he sets out to join the fraternity, his brother exhibits reservations, a sentiment that threatens to divide them. The stakes violently increase with a series of torturous and humiliating events.